Analisis Komparasi Kinerja Keuangan Bank Umum Konvensional dan Bank Umum Syariah - Ririn Setyaningsih; Siti Resmi (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2020)
The awareness of the Indonesian public to transact through Syaria banks is increasing. This condition is likely to affect the financial performance of conventional banks and Syaria banks. This study aims to analyze the differences in the financial performance of conventional banks and Syaria banks. The analysis used is based on two approaches, namely based on the ratio ranking criteria according to Regulation No.13/24/DPNP and the statistical approach. The analysis based on the ratio ranking shows that the financial performance of conventional banks is better than Syaria banks, both in terms of risk profile assessment, profitability, and capital. Analysis with a statistical approach includes normality test and difference test. The results of the normality test using One Sample Kolmogorov-Smirnov show that the significance value for net performing loan (NPL), loan to deposit ratio (LDR), return on assets (ROA), and Capital Adequacy Ratio (CAR) is 0.001; 0.225; 0.022; and 0.004. This means that the LDR data is normally distributed, while NPL, ROA and CAR are not normally distributed. Different tests for NPL, ROA and CAR using the Mann Withney test showed that the significance value for the three ratios was 0.000 for each ratio. Different test for LDR using independent sample t-test, obtained a significance value of 0.003. Overall, the financial performance shown by LDR, NPL, ROA and CAR between conventional banks and Syaria banks is different.